Cognitive skills and the LOGSE reform in Spain: Evidence from PIAAC - José A. Robles-Zurita (SERIEs - Journal of the Spanish Economic Association, 2017)
We use data from the Spanish sample of the Programme for the International Assessment of Adult Competencies to analyze the effect of the LOGSE (Spanish acronym for General Law of the Education System) reform passed in 1990 on numeracy and literacy proficiency of the adult population. The LOGSE effect is identified by exploiting the variability of the rate of implementation among cohorts and regions. The results change depending on the specification of the econometric model and mainly on the type of birth year trend assumed. Nonetheless, overall results suggest that the LOGSE reform did not help to increase cognitive skills of the population despite an extension of compulsory years of education and postponement of the age of initial tracking into vocational and academic studies.
Keywords: I20; J240; 330; LOGSE; PIAAC; Education reform; Compulsory education; Vocational